CHARACTERISTICS OF RADIO TEXT - Jabborova Hamida (Galaxy International Interdisciplinary Research Journal, 2022)
Speaking about the radio text, the researchers note that it is "a mental-verbal complex, complicated by the polycode nature of implementation, created in an institutionally organized information and communication environment, reflecting social reality and influenced by its context", embodies the image of the addressee and creates certain fragments in his mind – forms views, beliefs, values, reflects the center of communicative, cognitive and socio-cultural projections, which includes removing these dynamic layers in the explanatory key of the research, presenting the results of mass media speech activity as a multi-component model. Speech on the radio is a form of oral speech in which the speaker embodies the language based on the reaction of the listener. On-air speech is a voice distribution of text, regardless of whether it is prepared or spontaneous – unprepared, sporadic (sudden) character.